Financial Credit Outcomes of IDA Participation: Longitudinal Findings - Julie Birkenmaier; Jami Curley; Patrick Kelly (Journal of Financial Therapy, 2015)
Financially vulnerable families often struggle with low credit scores. Thus, improved participant credit is often a goal of asset development programs, such as the Individual Development Account (IDA) program, but little is known about the long-term credit outcomes of participation. This article reports the final results of a three-year longitudinal exploratory study of credit outcomes for IDA participants. Using a convenience sample of IDA participants and non-participants (N = 164), data were analyzed using nonparametric and Chi-square for independence tests. Results indicate that participant credit scores improvements are achieved and maintained. Credit score is not a meaningful indicator of program completion, time to completion, or type of asset purchased for participants. Those who completed the IDA program within two years experienced the highest credit gains. Future research with larger samples is needed to further assess the impact of credit scores on program participation and completion.
Keywords: Longitudinal; Credit; Asset Developmeis nt; Individual Development Account; Credit Score